Deflating the deflationary view of information - Lombardi, Olimpia Iris (2016)
Christopher Timpson proposes a deflationary view about information, according to which the term information is an abstract noun and, as a consequence, information is not part of the material contents of the world. The main purpose of the present article consists in supplying a critical analysis of this proposal, which will lead us to conclude that information is an item even more abstract than what Timpson claims. From this view, we embrace a pluralist stance that recognizes the legitimacy of different interpretations of the concept of information.